Intereconomics Review of European Economic Policy - Breuer, Christian; Bourguignon, Jiffer; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Intereconomics publishes papers dealing with economic and social policy issues in Europe respectively in Euroland. The journal consists of the sections editorial, forum and articles. The editorial section contains brief comments on current questions of economic policy in Europe or effecting Europe. In the forum, several authors (researchers, politicians, representatives of trade unions and of employers associations etc.) voice their opinions on one particular current economic policy problem effecting Europe. The articles deal with economic policy issues and trends in Europe. They are mostly written by researchers in economics. Officially cited as: Intereconomics.
Keywords: European Economic Community literature; Economic policy; Social policy; Labor economics; Economic Policy; European Integration; Social Policy; Labor Economics